2021
DOI: 10.18805/lr-4757
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Morphological and Molecular Genetic Diversity in Pigeonpea [Cajanus cajan (L.) Millspaugh]

Abstract: Background: The estimation of genetic diversity in pigeonpea is crucial for desiging breeding programmes and germplasm conservation. Morphological studies alone do not provide sufficient information to understand genetic diversity. Molecular analysis using SSRs can provide additional information on genetic diversity that can be used for selection of diverse parents. Methods: The experimental material for present study consisted of 50 diverse genotypes of pigeonpea. The fifty genotypes were planted in Randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The minimum diversity was contributed by pods/plant (2.38%) followed by primary branches/plant (4.76%), days to 50% flowering (6.19%) and plant height (8.10%). This is in conformity with Naing et al [12] when they reported that more contribution towards genetic diversity for pigeon pea are days to maturity, pods/plant, days to 50% flowering and seed yield; Ranjani et al [8] observed that maximum contribution towards the genetic diversity for the traits i.e., 100-seed weight and days to maturity; Sandeep et al [14] reported maximum contribution for seed yield, 100-seed weight and days to 50% flowering [15].…”
Section: Clusters Mean and Percentage Contribution For Different Trai...supporting
confidence: 94%
See 1 more Smart Citation
“…The minimum diversity was contributed by pods/plant (2.38%) followed by primary branches/plant (4.76%), days to 50% flowering (6.19%) and plant height (8.10%). This is in conformity with Naing et al [12] when they reported that more contribution towards genetic diversity for pigeon pea are days to maturity, pods/plant, days to 50% flowering and seed yield; Ranjani et al [8] observed that maximum contribution towards the genetic diversity for the traits i.e., 100-seed weight and days to maturity; Sandeep et al [14] reported maximum contribution for seed yield, 100-seed weight and days to 50% flowering [15].…”
Section: Clusters Mean and Percentage Contribution For Different Trai...supporting
confidence: 94%
“…These results indicated that if hybridization is attempted between the genotypes included in these cluster, lot of genetic diversity will be produced in the segregating generation and the selection for desirable genotypes can be practiced. The greater intercluster distance as comparison to intra-cluster distance was also reported by previous workers Bisht et al [11], Naing et al [12] and Pushpavalli et al [13]. The maximum inter-cluster distance (16.54) between the cluster II and cluster VI followed by cluster IV and VI with the distance (14.34) and Cluster III and VI (13.22) indicating that genotypes from these clusters were highly divergent and hence selection of parents for hybridization from these clusters is suggested for realization of maximum heterosis.…”
Section: Genetic Diversitysupporting
confidence: 83%
“…Even though India is the largest producer of black gram, its average productivity and per cent contribution towards the total pulse production is less due to the lack of genetic variability, unavailability of potential ideotype, poor harvest index and lack of resistances to biotic and abiotic stresses (Devi et al, 2020). These constraints are due to ingeminate usage of related parents in hybridization programmes (Jayamani and Sathya, 2013) and breeding for few economic traits to reach the targets of market requirements (Naing et al, 2022). Hence, to develop the cultivars with wide genetic base, there is a need to estimate the genetic divergence among the available black gram germplam.…”
mentioning
confidence: 99%